Faktor - Faktor Yang Memengaruhi Nilai Perusahaan Property, Real Estate, Dan Building Construction - Angelica Novia, Linda Santioso (Fakultas Ekonomi, Universitas Tarumanagara, 2019)
The purpose of the research is to empirically examine the effect of intellectual capital, auditing quality, institutional ownership, financial performance, and leverage on firm value of the property, real estate, and building construction companies listed on the Indonesia Stock Exchange period 2015-2017. This research uses a sample of 41 companies that selected using purposive sampling method.The period of this research is 2015-2017. Eviews version 9.0 is used to processed data for analysis and hypothesis test. The result of this research are institutional ownership and financial performance have a significant effect on firm value. Intellectual capital, auditing quality, and leverage does not have a significant effect on the firm value